2019
DOI: 10.1139/juvs-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

A workflow to minimize shadows in UAV-based orthomosaics

Abstract: Shadows from buildings, terrain, and other elevated features represent lost and (or) impaired data values that hinder the quality of optical images acquired under all but the most diffuse illumination conditions. This is particularly problematic in high-spatial-resolution imagery acquired from unmanned aerial vehicles (UAVs), which generally operate very close to the ground. However, the flexibility and low cost of re-deployment of the platform also presents opportunities, which we capitalize on in a new workf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…With the reported coefficients of determination ranging from 0.39 to >0. 90, information from RGB sensors shows promise for estimation of vegetation AGB.…”
Section: Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…With the reported coefficients of determination ranging from 0.39 to >0. 90, information from RGB sensors shows promise for estimation of vegetation AGB.…”
Section: Indexmentioning
confidence: 99%
“…One study also found significantly more error in the horizontal and vertical positioning accuracy of point clouds created using imagery collected during cloudy conditions versus clear conditions and reported that although point clouds from cloudy days had higher point density than clear lighting conditions, they had lower canopy penetration and increased computing time [55]. However, very bright light creates dark shadows in imagery, decreasing the quality and utility of models in dark areas [90]. In addition, changing light conditions during data collection, even in close to nadir lighting, can introduce bidirectional reflectance distribution function effects, resulting in decreased data quality [3,66,72].…”
Section: Environment and Weather Conditionsmentioning
confidence: 99%
“…UAV data were collected on 13 September 2019. To minimise the impact of shadowed areas on image quality (Rahman et al, 2019 ; Stow et al, 2019 ), the flight was undertaken at noon. Flight paths were in a grid pattern, with a total flight distance of 14,059 m. The flight took approximately 40 min, with a total of 1269 images captured by each sensor.…”
Section: Methodsmentioning
confidence: 99%
“…These factors could influence covariates related to soil water content. Others have found that it is best to conduct drone surveys around noon to get the best lighting, minimize shadows and get similar illumination for all parts of the field [74]. This brings to light another drawback of frequent drone flights in an urban environment in heavily used fields.…”
Section: Rmses For Drone Datamentioning
confidence: 99%